Loyalitas pelanggan terhadap Produk Starbucks ditinjau dari Dimensi Ekuitas Merek (Pada Starbucks di Solo Square Surakarta) - Muhammad Rian Kisara; Bambang Mursito; Drs Djumali (JURNAL ILMIAH EDUNOMIKA, 2020)
The aim of this research are: to find out the simultaneous and partial influence of brand awareness, brand loyalty, brand association, and quality perception on Starbucks customer loyalty. The sample in this study were 75 Starbucks customers. Data collection techniques in this research were using observation, documentation , and questionnaires.Technical data analysis in this research were using classic assumption test, multiple linier test, ttest, ftest, the coefficients determined. The result of this study showed that there are simultaneous and partial influences of brand awareness, brand loyalty, brand association, and quality perception on Starbucks customer loyalty. Key words: brand awareness, brand loyalty, brand association, quality perception, and customer loyalty